Ecoprint Training on Tote Bags as a Means of Creative Education for Children in Dondong Village, Kesugihan District - Fuzzaman, Ari; Mukaromah, Alfi; Pratama, Muhammad Rafli Nur; Zahrani, Shelika; Virly, Al Vara Khoerul; Aisyah, Nadhatul Siti; Azizah, Lulu Nur; Taufik, Nahzah Intan Maulida; Hilwani, Almas Zeti; Putri, Arum Ifana; Susanti, Rini Puji; Kartikawati, Ratna (Proceedings Series on Social Sciences & Humanities, 2025)
Community service programs provide a vital opportunity for university students to apply their knowledge to address societal needs. This article details a community service initiative focused on enhancing creativity and environmental awareness among elementary school children in Dondong Village. The program utilized a training workshop on the ecoprint technique on tote bags. This activity was structured using the Participatory Action Research (PAR) approach encompasses sequential stages such as planning, implementing actions, conducting observations, and carrying out reflections. The chosen ecoprint technique was pounding, due to its simplicity and safety for children. The results indicated that the training was highly effective; all 20 participants successfully created unique ecoprint tote bags. The program significantly improved children's fine motor skills, creativity, and self-confidence. Furthermore, it successfully cultivated an early appreciation for utilizing natural resources in an environmentally friendly manner. The conclusion is that ecoprint training is a suitable and impactful creative educational tool for children, with strong potential for future development.